Comparative evaluation of structure and characteristic of peptidyl-prolyl cis-trans isomerase proteins and their function in Salmonella Typhimurium stress responses and virulence - Kumawat, Manoj; Singh, Piyush Kumar; Rananaware, Supriya Rajendra; Ahlawat, Sushma (Folia microbiologica, 2020)
Peptidyl-prolyl cis-trans isomerases (PPIase) exhibit chaperone activity and assist in protein folding by increasing the rate of cis-trans transition on proline-peptide bonds. The current study aimed to identify and characterize three genes, ppiA, ppiB, and ppiC, which encode proteins of the PPIase family in the bacterium Salmonella enterica serovar Typhimurium. Salmonella Typhimurium is a facultative intracellular zoonotic pathogen that causes food- and water-borne gastroenteritis in humans (leading to bacteremia in immune-compromised subjects). Recombinant clones for the three genes were constructed and sequenced and the sequences submitted to NCBI GenBank. Three-dimensional structures for the corresponding proteins were predicted by comparative modeling. A maximum-likelihood phylogenetic gene tree constructed for the three genes showed a low evolutionary mean diversity, indicating strong evolutionary conservation. Further, single-gene deletion mutant strains, generated for the respective genes, were observed to be more susceptible to the stationary phase of growth and heat stress conditions and showed reduced survival within macrophage cells line. The present study thus indicates that ppiA, ppiB, and ppiC genes are conserved among Salmonella genome, are critical for the growth of Salmonella Typhimurium in the examined stress conditions, and may play a role in its responses and virulence.
Keywords: genom bakteriální; peptidylprolylisomerasa; Peptidylprolyl Isomerase; Salmonella Typhimurium; ppiC and stress responses; Stress, Physiological; virulence; ppiB; fyziologický stres; ppiA; kur domácí; Bacterial Proteins; Chickens; zvířata; Virulence; Salmonella typhimurium; fylogeneze; Peptidyl-prolyl cis-trans isomerases; bakteriální proteiny; Genome, Bacterial; salmonelová infekce u zvířat; Phylogeny; Salmonella Infections, Animal; Animals